1990
DOI: 10.1002/jcp.1041420326
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐colony‐stimulating factor (CSF‐1) modulates a differentiation‐specific inward‐rectifying potassium current in human leukemic (HL‐60) cells

Abstract: A voltage-activated inward-rectifying K+ conductance (lKi) appears in human promyelocytic leukemia (HL-60) cells during phorbol ester-induced differentiation into macrophages. This conductance was detected in the cells 24 hours after exposure to phorbol-12-myristate-13-acetate (PMA), as the cells began to express the macrophage phenotype, and continued to increase for 4 days after PMA exposure. The magnitude of inward current was a function of external K+; current was blocked by extracellular or intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Given the functional similarities between macrophages and neutrophils, as well as their derivation from a common precursor, it seems plausible that they would be similar in their ion channel expression profile. However, the human promyelocytic cell line HL-60 expresses Kir2 channels when it is differentiated into macrophages but not into granulocytes (56), possibly indicating that there are important differences in ion channel expression between the two phagocytic lineages in humans.…”
Section: C272 Kir21 Channels In Mouse Neutrophilsmentioning
confidence: 99%
“…Given the functional similarities between macrophages and neutrophils, as well as their derivation from a common precursor, it seems plausible that they would be similar in their ion channel expression profile. However, the human promyelocytic cell line HL-60 expresses Kir2 channels when it is differentiated into macrophages but not into granulocytes (56), possibly indicating that there are important differences in ion channel expression between the two phagocytic lineages in humans.…”
Section: C272 Kir21 Channels In Mouse Neutrophilsmentioning
confidence: 99%
“…C ell cycle-dependent changes in K ϩ current expression have been studied more directly in a few cell preparations, which provide evidence for a loss of K IR activity during proliferation, consistent with our data. For example, proliferating human leukemia cells generally lack expression of K IR currents, but currents are upregulated rapidly on induction to differentiate into macrophages (Wieland et al, 1990). Mouse embryos (Day et al, 1993), HeLa cells (Takahashi et al, 1994), and neuroblastoma cells (Arcangeli et al, 1995) all exhibit a downregulation of K IR currents on entrance into S-phase of cell cycle.…”
Section: Electrophysiological Changes In Gliosis Mirror Those Associamentioning
confidence: 99%
“…Studies have shown the presence of different types of ion channels in blood cells, including inwards and outwards rectifying K channels, mechanosensitive cation channels, Cl and Na channels and a Ca-dependent Na channel regulated by the actin cytoskeleton [2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%